Is Good Governance Good for Development? (Bloomsbury Academic, 2022)
This book is available as open access through the Bloomsbury Open Access programme and is available on bloomsburycollections.com. While good governance is a worthy goal, this book argues that it is not a prerequisite for economic growth or development. The book exposes the methodological shortcomings of the commonly-used governance indicators developed within the World Bank. The authors argue that donors should not impose onerous good governance conditions, expecting the developing world to simulate now-developed countries. They contend that most poor countries lack the administrative and financial capacity to achieve these reforms or institutions - so donor conditionality often becomes a recipe for failure. In place of grand government reforms aimed at enhancing market efficiency, the book's position is that the reform agenda should target strategic bottlenecks for development and enhance the state's capacity to deal with these disruptions. Bringing together contributions from leading political scientists, political economists and development practitioners, this is the first book to provide a systematic critical perspective on received notions of good governance.